Anisotropic Low‐Dimensional Materials for Polarization‐Sensitive Photodetectors: From Materials to Devices. Issue 6 (21st January 2022) - Wang, Jing; Jiang, Changzhong; Li, Wenqing; Xiao, Xiangheng
Abstract: Polarization‐sensitive detectors based on anisotropic low‐dimensional materials have been widely investigated in recent years. Some low‐dimensional materials possess anisotropy characteristics owing to their low‐symmetry intrinsic crystal structures or external geometry morphology exhibiting distinct anisotropic vibrational, optical, electronic, and electrical properties. In general, the polarization state of light will change with certain regularity when polarized light interacts with the anisotropic medium. Therefore, low‐dimensional materials are very suitable for the preparation of polarization‐sensitive photodetectors. Here, an overview of recent development in polarization‐sensitive photodetectors based on anisotropic systems is presented. The classification and anisotropic properties of low‐dimensional materials are presented and the characterization of anisotropy is highlighted. Particularly, the anisotropic characteristics of different material systems from the perspective of crystallography are analyzed and the working mechanism of polarization‐sensitive photodetectors is discussed. Then, the recent advances of low‐dimensional materials‐based polarization‐sensitive photodetectors are reviewed in detail. Finally, a summary for this review is made and some breakthroughs for future development in this burgeoning field are addressed. Abstract : Polarization‐sensitive photodetectors based on anisotropic low‐dimensional materials have attracted much concern for their excellent performance, especially unique polarization sensitivity due to their anisotropic properties. This review intends to give an overview of the recent advances in polarization‐sensitive photodetectors based on anisotropic low‐dimensional materials from materials and their properties to devices.